Characteristics of energetic electron precipitation associated with chorus emissions and pulsating aurora observed at Syowa Station: A case study on 17 May 2007 - Tadokokoro , Hiroyasu; Ozaki, Mitsunori; Katoh , Yuto; Miyoshi , Yoshizumi; Yamagishi, Hisao; Kadokura, Akira; Tanaka, Yoshimasa (2012)
第3回極域科学シンポジウム/第36回極域宙空圏シンポジウム 11月26日（月）、27日（火） 国立極地研究所 2階ラウンジ conference object